Proceso de atención de enfermería en paciente adulto con herida de arma blanca en región abdominal. - Angulo Bayas, Daira Valeria (2022)
The development of this clinical case of a 31-year-old male patient with a penetrating wound by stab wound, the wound is classified as a body injury that causes damage to the affected area, the wound may be located on the surface of the skin or may be affecting any organ. The abdominal trauma due to white wound is represented in 8% in our country, among the most affected organs are the liver in 31%, small intestine 20%. The objective of this case is detailed in the application of the nursing care process in addition to applying other interventions to assist the needs evidenced by the altered functional patterns, the application of theories such as M. Gordon, Nanda, Nic, Noc, in this way complementary examinations were applied to determine a definitive diagnosis and apply the appropriate treatment such as antibiotherapy and pain therapy, in conclusion, the nursing diagnosis was evidenced in an adult patient with white wound in the abdominal region, where it was necessary to apply complementary examinations such as laboratories which allowed to diagnose the severity of the case having complications of organs such as grade III liver trauma.